An Analysis of the Relevance of Instructional Material and Types of Teaching Strategies used for Reading 1 Course in English Education Department - ., Ni Made Evi Agustini; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Dra.Ni Made Ratminingsih, MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menganalisa relevansi dari materi pembelajaran dengan silabus dan tipe dari penggunaan strategi mengajar untuk mata kuliah Reading 1 di Jurusan Pendidikan bahasa Inggris. Subjek dari penelitian ini adalah para dosen pada mata kuliah Reading 1 di Jurusan Pendidikan Bahasa Inggris, Universitas Pendidikan Ganesha. Penelitian ini adalah penelitian deskriptif kualitatif dengan menggunakan daftar cek. Data dikumpulkan dari hasil daftar cek para dosen dan penguji ahli. Data didapatkan dengan analisa deskriptif. Temuan dari penelitian ini menunjukkan relevansi dari materi pembelajaran dan kriteria dari materi pembelajaran yang baik pada level "Sedikit relevan" untuk digunakan sebagai sumber belajar siswa Jurusan Pendidikan Bahasa Inggris. Berdasarkan hasil analisis dari dua penguji ahli yang menyatakan 30% dari kriteria yang telah tercapai. Strategi pengajaran yang sering digunakan pada mata kuliah Reading 1 adalah small group work, problem solving, cooperative group, performance activities, writing and inquiry based learning. Kata Kunci : kemampuan membaca, materi pembelajaran, strategi pembelajaran This research was conducted to analyze the relevance of instructional materials to the syllabus and the types of teaching strategies used for Reading 1 course in English Education Department. The subjects of the study were the lecturers in Reading 1 course of English Education Department, Ganesha University of Education. This research was a descriptive qualitative research by utilizing checklist. The data were collected from the lecturers and expert judges’ checklist. The data obtained were descriptively analyzed. The finding of the research showed the relevance of Instructional Materials and the criteria of a good material in the level of “Slightly Relevant” to be used as learning resource for English Education Department students. Based on the result of analysis from two expert judges stated 30% of criteria which had been reached. The teaching strategies that used frequently in Reading 1 course were small group work, problem solving, cooperative group, performance activities, writing and inquiry based learning.keyword : instructional material, reading skill, teaching strategies